Sociocultural Curriculum Design in Islamic Education: Insights from a Local Wisdom Based Approach in West Java - Ceceng Saepulmilah; Tatang Muh Nasir; Rizwan Martiadi; Dadang Komara; Siti Aini Latifah Awaliyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the integration of local Sundanese cultural values into the Islamic Religious Education (PAI) curriculum through a sociocultural approach. In Indonesia’s multicultural context, aligning Islamic teachings with local wisdom is essential to make religious education more meaningful and contextually relevant. Employing a qualitative descriptive design, data were collected through literature analysis, classroom observations, and semi-structured interviews with four PAI teachers at SMPN 1 Kadipaten, Tasikmalaya Regency, West Java. Additional data sources included school documents and extracurricular activity reports. Thematic analysis was conducted to identify patterns of curriculum integration, teaching strategies, and student character development. Findings reveal that Sundanese values—silih asah (mutual learning), silih asih (compassion), and silih asuh (nurturing)—were systematically embedded into core Islamic competencies such as akhlaq, muamalah, and fiqh. These values enhanced students’ engagement in religious and social activities, improved discipline, empathy, and social responsibility, and fostered collaboration among schools, families, and communities. Authentic assessments were used to evaluate behavioral outcomes. The sociocultural model provides a culturally grounded and pedagogically effective framework for character education in Islamic contexts. Despite challenges such as limited instructional time and lack of standardized modules, teacher initiative played a critical role in successful implementation. The study suggests this model can serve as a reference for other culturally rich regions in designing meaningful Islamic curricula.